Tectonics Inversions, Fault Segmentation, and Triggering Mechanisms in the Central Apennines Normal Fault System: Insights From High‐Resolution Velocity Models. Issue 11 (7th November 2018) - Buttinelli, M.; Pezzo, G.; Valoroso, L.; De Gori, P.; Chiarabba, C.
Abstract: The potential role of subsequent tectonic phases in reworking inherited geological structures is a key issue to unravel the seismotectonics of an area. This has a direct connection with fault segmentation, earthquakes maximum magnitude, and strong implications for seismic hazard assessment. The central Apennines (Italy) represent an exemplary case, since it developed because of the overprint of different deformational phases, producing potential conditions for episodic tectonic inversions and a very complex structural architecture. In this paper, we show how inherited compressional structures, still dominating the Apennines belt architecture, interfere with the active extension, having a direct connection with active seismotectonics. We present seismicity and new velocity tomograms of an 80‐km‐long section of the normal fault system activated during the 2009 and 2016–2018 seismic sequences. The joint interpretation highlights how the extensional seismic sequences partially reactivated inherited compressive structures, which have not an undisputable relationship with the surficial geological setting. Complexity deriving from the irregular geometry of normal faults and inverted thrust ramps is responsible for the observed intense fragmentation of the extensional system. Fluid overpressure seems to be a viable mechanism behind the partial remobilization of unbroken segments of the fault system. Key Points: Tectonic inversions and fault segmentations represent the main process behind the current crustal arrangement of central Apennines Surface versus deep expression of faults: subsequent deformational stages cause complex interaction between inherited extensional and compressional structures Fluid overpressure plays a role in the partial remobilization of unbroken fault segments